BENEFITS AND SAFETY OF INSULIN THERAPY IN PEDIATRIC AND ADOLESCENT PATIENTS SUFFERING FROM CYSTIC FIBROSIS-RELATED DIABETES MELLITUS (CFRD): A SYSTEMATIC REVIEW - I Gusti Agung Nyoman Indira Prana; Fauna Herawati (INFOKUM, 2022)
About 40% of conditions of glucose intolerance occur in children aged 6-10 to adolescents with cystic fibrosis who are deficient in insulin. Hyperglycemia can occur before a person with cystic fibrosis is diagnosed with CFRD, with a significant reduction in clinical patients in glucose intolerance and an increased risk of lung organ failure. This systematic study aimed to determine the benefits and safety of providing insulin therapy in children and adolescents with Cystic Fibrosis-related Diabetes Mellitus (CFRD). The process of searching published literature through online databases such as Pubmed, Cochrane Library, ScienceDirect, and Google Scholar using the keywords Children, Insulin, Cystic Fibrosis, and Diabetes Mellitus using the Boolean operator "AND". A total of eight studies were selected with criteria not limited to just the type of RCT, patients with an age range of 1 month -18 years were diagnosed with Cystic Fibrosis-related Diabetes Mellitus (CFRD), and compared with insulin therapy with placebo, other OAD, or no therapy. From the eight kinds of literature that were reviewed systematically, it was shown that the administration of insulin therapy had benefits in improving the clinical status of the patient, such as decreasing the% HbA1c value, increasing FEV1, and improving the patient's nutritional status through the patient's BMI parameter, besides that insulin therapy was considered safe and tolerable by children and adolescents suffering from Cystic Fibrosis-related Diabetes Mellitus.